Acute Oral Toxicity studies on Ethanol Extract of Aerial Parts of Blumea laevis (EABL) in Rats - Kumar, Yashas R.; Nair, Divakaran N.; R., Anoopraj; K.S., Prasanna; Palekkodan, Hamza; George, Ajith Jacob; Rani, Suja (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Acute toxicity test of ethanol extract of aerial parts of Blumea laevis (EABL) plant material was studied in female Sprague-Dawley rats owing to lack of studies on toxicity of B. laevis plant. The in-vivo acute oral toxicity EABL in Sprague Dawley rats was carried out as per OECD guidelines 425. Results revealed that there was no significant difference (p>0.05) in feed intake in both the treatment groups (i.e., 1750 & 5000 mg/kg) even though water intake was significantly higher (p
Keywords: Acute toxicity; Blumea laevis; Ethanol extract; Sprague-Dawley rats